Phase transformations in WB36 heat resistant steel under continuous cooling conditions. (July 2013) - Zhang, D. T.; Qiao, Z. X.; Yang, X.; Ning, B. Q.; Liu, Y. C.; Yan, Z. S.
Abstract : Aiming to optimise the thermal treatment technology of WB36 heat resistant steel, the characteristics of phase transformations during continuous cooling at 5–2000°C min −1 were investigated by means of microstructure observation and dilatometric measurements. The continuous cooling transformation diagram of WB36 heat resistant steel was obtained, as well as the fractions of different transformation products obtained under various cooling conditions. The results showed that the transformation products in continuously cooled WB36 heat resistant steel involve polygonal ferrite, pearlite, granular bainite and lath martensite, with increasing cooling rates from 5 to 2000°C min −1 . Owing to the Mo addition to the steel, the super cooled austenite in WB36 heat resistant steel was stabilised significantly, and granular bainite can be obtained in a wide range of cooling rate. However, the substructures of granular bainite vary significantly with the increase in cooling rate, including matrix morphology and the distribution of M/A islands in the matrix.